2017
DOI: 10.1037/hea0000423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dyadic planning on physical activity in couples: A randomized controlled trial.

Abstract: Findings revealed the complexity of effects of dyadic planning on behavior change. Adding relationship quality to the equation clarified effects of DPC and IPC on physical activity. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 33 publications
3
65
0
Order By: Relevance
“…This study represents secondary analyses of a larger randomised controlled trial with couples. Results of the randomised controlled trial had been already published elsewhere (Knoll et al., ; trial registration #NCT01963494, https://clinicaltrials.gov/). The primary goal of the randomised controlled trial was to examine whether a dyadic planning intervention is more effective than an individual planning intervention and a dyadic control condition in helping couples change their daily physical activity (for the short‐term results please see Knoll et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study represents secondary analyses of a larger randomised controlled trial with couples. Results of the randomised controlled trial had been already published elsewhere (Knoll et al., ; trial registration #NCT01963494, https://clinicaltrials.gov/). The primary goal of the randomised controlled trial was to examine whether a dyadic planning intervention is more effective than an individual planning intervention and a dyadic control condition in helping couples change their daily physical activity (for the short‐term results please see Knoll et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Results of the randomised controlled trial had been already published elsewhere (Knoll et al., ; trial registration #NCT01963494, https://clinicaltrials.gov/). The primary goal of the randomised controlled trial was to examine whether a dyadic planning intervention is more effective than an individual planning intervention and a dyadic control condition in helping couples change their daily physical activity (for the short‐term results please see Knoll et al., ). One week after a baseline assessment (T0), the intervention session took place (Time 1 [T1]), where couples were randomly assigned to one of the three experimental groups and also randomly received a specific study role (partner or target person; for more details, see Knoll et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An as yet unexplored area of investigation with regard to action planning in the context of safer sex behaviour is the effect of dyadic planning. Research looking at the effects of action planning on physical activity behaviour has identified that making a plan with a partner is linked to higher levels of plan enactment (Keller et al., ; Knoll et al., ). Consideration of social aspects of planning including dyadic planning has also been recommended as a priority for future research in the field of action planning and implementation intentions (Hagger et al., ).…”
Section: Discussionmentioning
confidence: 99%